Regional Retribution Collection as the uses of foreign workers at Department of Labor, Population Resettlement, and Cooperatives - Banten Province - Pratiwi, Refi; Mulyanah; Puspanita, Intan; Suryani , Lusi (PT Larva Wijaya Penerbit, 2023)
The purpose of this paper is to find out the technical collection and payment of regional fees for foreign workers at the department of labor, population resettlement, and cooveratives of Banten Province. The research method used descriptive method analysis. The data used in this paper are primary data and secondary data. The data source comes from internal data obtained from department of labor, population resettlement, and cooveratives of Banten Province. The data collection methods are interviews, documentation, observation, and literature study. The result of this research shows that the collection technique Regional fees for the use of foreign workers at the Office of Manpower and Transmigration of Banten Province are collected based on Regional Regulation of Banten Province Number 1 of 2018 which are collected using Regional Retribution Letters (SKRD) or other documents.